2008
DOI: 10.1021/jm701344b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Opioid Receptor Functional Antagonism of Analogues of the Selective Kappa Opioid Receptor Antagonist (3R)-7-Hydroxy-N-((1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic)

Abstract: In previous structure-activity relationship (SAR) studies, we identified (3 R)-7-hydroxy- N-((1 S)-1-{[(3 R,4 R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic, 1) as the first potent and selective kappa opioid receptor antagonist from the trans-3,4-dimethyl-4-(3-hydroxyphenyl)piperidine class of opioid antagonist. In the present study, we report the synthesis and in vitro opioid receptor functional antagonism of a number of analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 31 publications
(64 reference statements)
3
48
0
Order By: Relevance
“…33 The nitro ( 41 ), acetylamino ( 42 ), methanesulfonylamino ( 43 ), and amino ( 44 ) analogues were 320-, 70-, 200-, and 10-times less potent as a κ antagonist than JDTic and were not as selective for the κ receptor relative to the μ and δ receptors as JDTic. The methoxy ( 45 ) analogue was only 3-fold less potent than JDTic as a κ antagonist.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…33 The nitro ( 41 ), acetylamino ( 42 ), methanesulfonylamino ( 43 ), and amino ( 44 ) analogues were 320-, 70-, 200-, and 10-times less potent as a κ antagonist than JDTic and were not as selective for the κ receptor relative to the μ and δ receptors as JDTic. The methoxy ( 45 ) analogue was only 3-fold less potent than JDTic as a κ antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we reported that 37 , which has a carboxamide group replacing the hydroxyl of the 4-(3-hydroxyphenyl) group, has a K e = 0.12 nM at the κ receptor, which was only 6 times less potent than JDTic as a κ opioid receptor (KOR) antagonist (Table 2). 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was achieved by refluxing the compound in acetone in the presence of Me 2 SO 4 and KHCO 3 . [21] The crude product was purified using column chromatography to obtain the desired compound 12 in a 80 % yield. Afterwards, deprotection of the Cbz group of 12 was accomplished and subsequent reduction to the amino alcohol afforded 14 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%